S-palmitoylation of MAP kinase is essential for fungal virulence - Yuhang Duan; Pingping Li; Deyao Zhang; Lili Wang; Yuan Fang; Hong Hu; Qiulu Mao; Xiaolan Zhou; Panpan Zhao; Xuechun Li; Jinfeng Wei; Jintian Tang; et al. (mBio)
ABSTRACT S-palmitoylation is an important reversible protein post-translational modification in organisms. However, its role in fungi is uncertain. Here, we found the treatment of the rice false fungus Ustilaginoidea virens with S-palmitoylation inhibitor 2 BP resulted in a significant decrease in fungal virulence. Comprehensive identification of S-palmitoylation sites and proteins in U. virens revealed a total of 4,089 S-palmitoylation sites identified among 2,192 proteins and that S-palmitoylated proteins were involved in diverse biological processes. Among the five palmitoyltransferases, UvPfa3 and UvPfa4 were found to regulate the pathogenicity of U. virens. We then performed quantitative proteomic analysis of ∆UvPfa3 and ∆UvPfa4 mutants. Interestingly, S-palmitoylated proteins were significantly enriched in the mitogen-activated protein kinase and autophagy pathways, and MAP kinase UvSlt2 was confirmed to be an S-palmitoylated protein which was palmitoylated by UvPfa4. Mutations of S-palmitoylation sites in UvSlt2 resulted in significantly reduced fungal virulence and decreased kinase enzymatic activity and phosphorylation levels. Simulations of molecular dynamics demonstrated mutation of S-palmitoylation sites in UvSlt2 causing decreased hydrophobic solvent-accessible surface area, thereby weakening the bonding force with its substrate UvRlm1. Taken together, S-palmitoylation promotes U. virens virulence through palmitoylation of MAP kinase UvSlt2 by palmitoyltransferase UvPfa4. This enhances the enzymatic phosphorylation activity of the kinase, thereby increasing hydrophobic solvent-accessible surface area and binding activity between the UvSlt2 enzyme and its substrate UvRlm1. Our studies provide a framework for dissecting the biological functions of S-palmitoylation and reveal an important role for S-palmitoylation in regulating the virulence of the pathogen.IMPORTANCES-palmitoylation is an important post-translational lipid modification of proteins. However, its role in fungi is uncertain. In this study, we found that S-palmitoylation promotes virulence of rice false smut fungus U. virens through palmitoylation of MAP kinase UvSlt2 by palmitoyltransferase UvPfa4. This enhances the enzymatic phosphorylation activity of the kinase, thereby increasing hydrophobic solvent-accessible surface area and binding activity between the UvSlt2 enzyme and its substrate UvRlm1. Our studies provide a framework for dissecting the biological functions of S-palmitoylation and reveal an important role for S-palmitoylation in regulating the virulence of the pathogen. This is the first functional study to reveal the role of S-palmitoylation in fungal virulence.